Hubungan Perilaku Menonton Drama Korea dengan Pembentukan Konsep Diri Pada Remaja di SMPN 1 Cileungsi - Diah Ratnawati; Vanda Gita Rahmadani (STIKes Surya Global Yogyakarta, 2021)
Background: In the digitalization era, social media become a tool to obtained information from over the world. The influence of Korean culture spread and become a favorite among adolescents. This study aims to determine the relationship between watching Korean Drama with the establishment of adolescent self-concept. Methods: The study design used in this study was a cross-sectional approach, with the sampling technique used simple random sampling technique. The study method used in this study was the Chi-Square Test. The sample of this study was 181 students in Cileungsi 1 Junior High School. Results: The calculation result obtained p-value = 0.000 that means there was a significant relationship between the behavior of watching Korean drama with self-concept establishment of adolescent, with Odds Ratio value = 0,066, it means that adolescent who have high addiction to watch Korean drama have opportunity 0,066 times higher to form the negative self-concept than the adolescent who has low addiction of watching Korean drama. Conclusion: Adolescents were expected can choose educative programs and suitable for their age, so they can imitate the positive behavior from the programs to form a positive self-concept. Keywords: Adolescent, Behavior of watching Korean Drama, Self-concept